Blended Finance and Its Role in Mitigating Financial and Business Risks for Social Enterprises: A Study of Healthcare Social Enterprises in India - Chakraborty, Gautam (Digital Repository of Theses, 2025)
[It is increasingly seen that the investments required for sustainable development cannot be met by the public or private entities on their own. The challenge is looking for ways that can bring together the private investments along with public funds through blended financing. There are very few blended finance platforms for supporting healthcare social enterprises, especially in countries like India. Hence, this research aims at studying the risks faced by the healthcare social enterprises and how blended finance, can address those risks, in the Indian healthcare context. The research uses qualitative case-study method and conceptual modeling, using grounded theory and framework analysis. Four case studies were developed covering different healthcare social enterprises that have adopted blended finance to de-risk their business and to accelerate the healthcare social impact in India. The social enterprises were selected for the case studies from a limited universe of such enterprises in India adopting blended finance. Data collection involved In-Depth Interview (IDI) of the healthcare social entrepreneurs and review of project documents, websites and other such information shared by the entrepreneurs. The study shows that social enterprises address social impact, business risks, financial risks, and business viability through innovative approaches that go beyond traditional understanding. The case studies hint at the importance of context in shaping social enterprise strategies, the crucial role of technology in enabling scale and efficiency, the significance of partnerships in risk management and the innovation in financial models, particularly blended finance. The study demonstrates that successful healthcare social enterprises combine innovative business models, strategic use of blended finance, strong focus on accessibility and affordability, effective use of technology and strategic partnerships. The study also indicates that blended finance mitigates risk faced by the social enterprises through financial risk reduction, operational risk management and market risk mitigation. In addition, the study shows blended finance helping the social enterprises address social impact by improving access, enhancing quality, achieving scale and supporting innovations. This is captured in a suggested conceptual model of how blended finance enables social enterprises address risks and impact, which can guide global investors looking to invest in social enterprises.]